TEKNIK STRENGTH BOMBARDMENT DALAM PERSPEKTIF BIMBINGAN KONSELING ISLAM - M, Nurhikmah; Nurjannah (Jurnal Dakwah Tabligh, 2023)
This study is motivated by the lack of literature review regarding the strength bombardment technique. Based on the results of the analysis, there are deficiencies and weaknesses in the concept and implementation of the strength bombardment technique. The implications of deficiencies and weaknesses trigger additional problems experienced by counselees such as anxiety, arrogance, and Suudzhon towards God’s destiny. So this paper comes as a development of a strength bombardment technique with the concept of nature as part of Islamic psychology that can be given to the process of providing assistance to Islamic guidance and counseling services. This article discusses strength bombardment techniques, the concept of nature, the concept of nature: Islamic psychology approaches and humanistic existential approaches, Islamic guidance and counseling, to the development of strength bombardment techniques with the nature concept of Islamic psychology. The results of this study indicate that the development of the strength bombardment technique not only solves the counselee’s problems but can increase the counselee’s piety, increase gratitude, make more sense of the problems experienced and live them with a husnudzhon attitude towards God’s destiny.